2020
DOI: 10.1021/acsami.9b20854
|View full text |Cite
|
Sign up to set email alerts
|

Bi and Sn Co-doping Enhanced Thermoelectric Properties of Cu3SbS4 Materials with Excellent Thermal Stability

Abstract: Cu3SbS4-based materials composed of nontoxic, low-cost, and earth-abundant elements potentially exhibit favorable thermoelectric performance. However, some key transport parameters and thermal stability have not been reported. In this work, the effects of Bi and Sn co-doping on thermoelectric properties and the thermal stability of Cu3SbS4 were studied by experiment and theoretical validation. Bi and Sn doping can effectively tune the electrical properties and the electronic band structure. The Bi and Sn dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The consequences of Sn doping have also been studied, including theoretical calculations, elastic characteristics, and thermal stability. 19 CuOdoped SnO 2 (SnO 2 :CuO) has been shown to have high sensitivity and selectivity in response to sensors. 20 For fungal sensing systems, the fabrication of high-performance electrode materials free of biological or chemical receptor labeling remains a critical difficulty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of Sn doping have also been studied, including theoretical calculations, elastic characteristics, and thermal stability. 19 CuOdoped SnO 2 (SnO 2 :CuO) has been shown to have high sensitivity and selectivity in response to sensors. 20 For fungal sensing systems, the fabrication of high-performance electrode materials free of biological or chemical receptor labeling remains a critical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…To boost biosensor performance, a layer of mesoporous SiO 2 was placed between a metal and graphene. , Sn doping may control the electronic band structure and electrical characteristics. The consequences of Sn doping have also been studied, including theoretical calculations, elastic characteristics, and thermal stability . CuO-doped SnO 2 (SnO 2 :CuO) has been shown to have high sensitivity and selectivity in response to sensors …”
Section: Introductionmentioning
confidence: 99%
“…This produced solar conversion efficiencies of less than 1%, , which are postulated to be the result of elemental Cu and other CAS impurities produced by an annealing process . Famatinite is conventionally synthesized by solid-state methods such as mechanical alloying coupled with either hot pressing or spark plasma sintering. , Nanoparticles have been synthesized using surfactant-mediated solvothermal and hot-injection routes, generally producing polycrystalline famatinite between 10 and 200 nm in size. , …”
Section: Introductionmentioning
confidence: 99%
“…A high power factor ( S 2 σ) and low thermal conductivity (κ) are necessary to improve the ZT of TE materials. Recently, several approaches have been proposed to enhance the ZT, such as band-structural engineering , by doping, , mechanical strain to enhance the Seebeck coefficient, and alloying and nanostructuring to reduce lattice thermal conductivity. It was reported that hydrogenated germanene (GeH) exhibited an extremely low thermal conductivity of 1.1 W/m·K caused by weaker interlayer interactions; thus, GeH is expected to have a high thermoelectric power factor .…”
Section: Introductionmentioning
confidence: 99%